The Role of Green Marketing in Enhancing Competitive Advantage within Service Industries - Liu, Shaowei (Pacific International Journal, 2024)
This study explores the role of green marketing in enhancing competitive advantage within service industries, focusing on the context of Beijing, China. Drawing on the Theory of Planned Behavior, the research investigates consumer attitudes, subjective norms, and perceived behavioral control towards green marketing practices, as well as their impact on competitive advantage indicators. A quantitative research design is employed, with data collected through a structured survey questionnaire from 300 respondents across three selected companies: Huawei Technologies Co., Ltd., China Mobile, and Bank of China. The findings reveal positive attitudes towards green marketing practices, strong subjective norms favoring environmentally responsible options, and a high level of perceived behavioral control in adopting green practices. Respondents perceive competitive advantages associated with green marketing, such as influencing product/service decisions and fostering innovation. The study contributes empirical evidence to the existing literature and offers practical implications for businesses seeking to formulate effective green marketing strategies to enhance their competitive position while contributing to environmental sustainability efforts.